2012
DOI: 10.1172/jci64516
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of GSK3β-mediated BACE1 expression reduces Alzheimer-associated phenotypes

Abstract: Deposition of amyloid β protein (Aβ) to form neuritic plaques in the brain is the pathological hallmark of Alzheimer's disease (AD). Aβ is generated from sequential cleavages of the β-amyloid precursor protein (APP) by the β-and γ-secretases, and β-site APP-cleaving enzyme 1 (BACE1) is the β-secretase essential for Aβ generation. Previous studies have indicated that glycogen synthase kinase 3 (GSK3) may play a role in APP processing by modulating γ-secretase activity, thereby facilitating Aβ production. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
239
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 360 publications
(253 citation statements)
references
References 107 publications
11
239
0
3
Order By: Relevance
“…As blockade of this AMPAR endocytosis has no effect on either basal synaptic transmission or the induction of LTP, our results support the notion that this AMPAR endocytosis may represent a feedback mechanism secondary to the increased synaptic efficacy during LTP. Although the mechanisms by which increased synaptic efficacy activates such a secondary AMPAR endocytosis are still unclear, Hou et al and others have recently reported a novel input-specific homeostatic downregulation of synaptic genic mice (referred to herein as AD mice) (36,37). As shown in Figure 6A, fEPSP recordings in vivo revealed that sHFS could only induce a decaying LTP that lasted for less than 1 hour in AD mice (aged 2.5 months) receiving control peptide infusion (scrGluA2 3Y , 3 μmol/kg, i.p.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As blockade of this AMPAR endocytosis has no effect on either basal synaptic transmission or the induction of LTP, our results support the notion that this AMPAR endocytosis may represent a feedback mechanism secondary to the increased synaptic efficacy during LTP. Although the mechanisms by which increased synaptic efficacy activates such a secondary AMPAR endocytosis are still unclear, Hou et al and others have recently reported a novel input-specific homeostatic downregulation of synaptic genic mice (referred to herein as AD mice) (36,37). As shown in Figure 6A, fEPSP recordings in vivo revealed that sHFS could only induce a decaying LTP that lasted for less than 1 hour in AD mice (aged 2.5 months) receiving control peptide infusion (scrGluA2 3Y , 3 μmol/kg, i.p.)…”
Section: Discussionmentioning
confidence: 99%
“…The other half of the brains was fixed in freshly depolymerized 4% paraformaldehyde and sectioned with a Cryostat (Leica) to 30-μm thickness for immunocytochemical staining as previously described (36,37). Every sixth slice with the same reference position was mounted onto slides for staining.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Recent data have also emphasized this possibility by showing that PKA stimulation using a cAMP phosphodiesterase inhibitor leads to an inhibition of GSK3␤ activity and attenuates A␤-induced tauopathy (72). GSK3␤ has also been shown to regulate A␤ production in vivo by controlling BACE-1 gene expression in a NFB-dependent manner (15); therefore, the inhibition of GSK3␤ activity following Syk inhibition may also contribute to the inhibition of A␤ and BACE-1 expression observed following Syk inhibition. Alternatively, Syk inhibition may also result in a suppression of NFB activation via an inhibition of RAF phosphorylation and AKT phosphorylation, which consequently is expected to lower BACE-1 expression and A␤ production.…”
Section: Discussionmentioning
confidence: 99%
“…Cdk5 has been shown to indirectly affect Tau hyperphosphorylation by regulating GSK3␤ activity establishing GSK3␤ as a key mediator of Tau phosphorylation at diseaseassociated sites (12). GSK3␤ appears to be a pivotal enzyme in AD as it regulates A␤ production and mediates pathological Tau hyperphosphorylation induced by A␤ (15)(16)(17).…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%
“…34 The inhibition of GSK-3b reduces the bsite APP cleaving enzyme 1-mediated cleavage of APP through a NF-jB signaling-mediated mechanism, which subsequently reduces Ab neuropathology and alleviates memory deficits in AD model mice. 35 In addition, the pathological activation of GSK-3b has been reported to induce apoptosis and is inhibited by phosphorylation. 36 Therefore, the up-regulation of p-GSK-3b inhibits its kinase's activity, and this may confer a protective effect on AD.…”
Section: Discussionmentioning
confidence: 99%